A comparison of activated charcoals for use in wines - Fenocchio, Paolo (Pesquisa Agropecuaria Brasileira, 2014)
Ten activated charcoals, seven Brazilian and three German, were compared to determine their efficiency in removing color, from five red wines of the Experimental Station of Bento Gonçalves, Rio Grande do Sul, Brazil, and also to evaluate their ash and iron contents. The charcoal most efficient in removing color was a German carbon, and which was followed by four Brazilian ones. The ash content of the charcoals varied from 0.33 to 13.0 per cent, and the iron content from 0.005 to 0.225 g per cent.